2014
DOI: 10.1002/jor.22611
|View full text |Cite
|
Sign up to set email alerts
|

External and internal bone micro‐architecture in normal and Kienböck's lunates: A whole‐bone micro‐computed tomography study

Abstract: Kienböck's disease is idiopathic osteonecrosis of the lunate, leading to its fracture and collapse. This study compares internal and external bone micro-architecture of normal and fractured lunates (Kienböck's), by using high-resolution three-dimensional (3D) micro-computed tomography (micro-CT) on the whole bone of the two lunate types, and histology. Fractured Kienböck-diseased lunates were obtained from patients undergoing proximal-row-carpectomy, while normal cadaveric lunates served as controls. 3D-micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The comparison of the in vivo micro-CT scan parameters of our Kienböck lunate with the in vitro findings of the Kienböck lunates excised in Low's previous studies 6, [13][14][15] revealed similar morphological values (►Tables 1 and 2). As for the trabecular microstructure parameters, the trabecular bone volume fraction, trabeculae number, and trabecular thickness showed higher values in our in vivo Kienböck lunate, which may indicate a more severe lunate collapse in our patient.…”
Section: Discussionsupporting
confidence: 64%
“…The comparison of the in vivo micro-CT scan parameters of our Kienböck lunate with the in vitro findings of the Kienböck lunates excised in Low's previous studies 6, [13][14][15] revealed similar morphological values (►Tables 1 and 2). As for the trabecular microstructure parameters, the trabecular bone volume fraction, trabeculae number, and trabecular thickness showed higher values in our in vivo Kienböck lunate, which may indicate a more severe lunate collapse in our patient.…”
Section: Discussionsupporting
confidence: 64%
“…The convex proximal surface subchondral bone plate is only a single trabecular layer. 12 Multiple trabeculae span the subchondral bone plate-transmitting the load and maintaining the height of the lunate. 12 This "at-risk" zone in the specimen in ►Fig.…”
mentioning
confidence: 99%
“…Demographic parameters and stage distributions were comparable among all treatment groups except when comparing the pre-operative stages in the RSO group and in the RSO and VBG groups. However, group classification according to the initial stage of KD was not performed for the following reasons: (1) it has been previously suggested that initial KD stage, according to Lichtman, has no influence on treatment outcome [ 25 , 26 ]; (2) the validity of current classifications has been questioned because arthritis of the lunate can be observed in the absence of lunate fracture or carpal collapse [ 1 ]; (3) the reliability and comparability of KD stages in literature is limited because no distinction is generally made regarding the localization of arthritis (lunate cartilage, lunate facet, or the entire radiocarpal joint) and because there is no consensus regarding the diagnostic requirements for KD and associated arthritis (X-ray, MRI, CT scan, or arthroscopy) [ 1 ]; (4) because KD may progress from a preserved lunate shape to fragmentation within 6 months [ 1 ], staging may not be accurate if more than 4 weeks have elapsed between diagnosis and surgery; (5) a correlation between radiological parameters of KD classifications and the clinical course has not been established, while many authors have observed a poor correlation with clinical findings [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found in a follow-up examination of 33 conservatively treated patients between stages II, IIIA, IIIB, and IV regarding ROM, DASH score, pain, or grip strength although the DASH score seemed to improve spontaneously in patients who had experienced symptoms for longer than 10 years [ 28 ]. The homogenous clinical outcomes of surgically treated patients may be due to partial wrist denervation during the procedures, limited specificity and sensitivity of outcome parameters, the relatively benign spontaneous course, insufficient statistical power, or a placebo effect.…”
Section: Discussionmentioning
confidence: 99%